2021
DOI: 10.1123/jsm.2020-0288
|View full text |Cite
|
Sign up to set email alerts
|

Critical Discourse Analysis as Theory, Methodology, and Analyses in Sport Management Studies

Abstract: Critical discourse analysis (CDA) is a theory, methodology, and type of analysis used across various fields, including linguistics, sociology, and philosophy. CDA focuses on how language is used; discourses are found within language, and knowledge is created through these discourses. CDA can be beneficial to sport management scholars who seek to question existing power structures. The purpose of this paper was to highlight the value and appropriateness of CDA for Journal of Sport Management readers in an effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…This finding indicates the potential of employing critical social science for expanding how research is conducted in the field. This potential has been discussed previously (Frisby, 2005), and sport management scholars specifically have suggested that variety in research methods and approaches could further strengthen the field (Olafson, 1995;Sotiriadou and Shilbury, 2010;van der Roest et al, 2015;Sveinson et al, 2021). Therefore, this finding provides further reasoning for employing a critical approach in sport management work and the value of such approaches for the field.…”
Section: Type Of Datamentioning
confidence: 54%
See 3 more Smart Citations
“…This finding indicates the potential of employing critical social science for expanding how research is conducted in the field. This potential has been discussed previously (Frisby, 2005), and sport management scholars specifically have suggested that variety in research methods and approaches could further strengthen the field (Olafson, 1995;Sotiriadou and Shilbury, 2010;van der Roest et al, 2015;Sveinson et al, 2021). Therefore, this finding provides further reasoning for employing a critical approach in sport management work and the value of such approaches for the field.…”
Section: Type Of Datamentioning
confidence: 54%
“…As mentioned in the introduction, sport sociology and general sociology journals publish critical work extensively, and therefore authors may find their critical sport management research is more welcomed in those outlets compared to sport management or business/administration outlets. Additionally, scholars have pointed to the tendency of sport management journals to privilege post-positivist work over more critical or qualitative approaches (e.g., Knoppers, 2015;Sveinson et al, 2021). Analyzing future trends can provide insight into the accuracy of the assumption that sport management journals are overall less open to publishing critical research.…”
Section: Journal Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…Critical discourse analysis as a methodology focuses on the use of language and the discourses within it and on understanding how knowledge is shaped through such discourses [55]. While it has been used in sport studies to analyze interviews [56], newspapers [57], and magazine articles [58], critical discourse analysis remains underutilized to analyze social media related to sport.…”
Section: Methodsmentioning
confidence: 99%